THE EFFECT OF AUDIT TECHNOLOGY LITERACY, PROFESSIONAL ETHICS, AND SELF-CONTROL ON THE AUDIT READINESS OF ACCOUNTING STUDENTS WITH AUDITOR CAREER INTEREST AS A MODERATING VARIABLE (Case Study of Accounting Students at Private Universities in Lamongan Regen - Nindy Ayu Khoiriyah; Isnaini Anniswati Rosyida; Moh. Ali Wafa (Escalate : Economics and Business Journal, 2026)
The digital transformation in audit practice has changed the competencies required of auditors in the modern era. Auditors are no longer only required to possess technical skills in the field of auditing, but also the ability to utilize audit technology, uphold professional ethics, and have good self-control in facing various professional challenges. This study aims to analyze the influence of audit technology literacy, professional ethics, and self-control on the audit readiness of accounting students with auditor career interest as a moderating variable. The study used a quantitative approach. The study population was students of the Accounting Study Program at a private university in Lamongan Regency, while the sample was determined using a purposive sampling technique according to predetermined criteria. The research data were obtained through the distribution of questionnaires using a five-point Likert scale. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. Testing included evaluation of the measurement model (outer model), the structural model (inner model), and testing the moderation effect. The results showed that audit technology literacy, professional ethics, and self-control influenced the audit readiness of accounting students. In addition, auditor career interest was proven to act as a moderating variable that strengthens the relationship between the independent variables and student audit readiness. These findings indicate that students' audit readiness is influenced not only by technical competency and behavioral aspects, but also by their motivation to pursue a career as an auditor. This research provides theoretical contributions to the development of auditing and behavioral accounting studies, and offers practical implications for universities in designing auditing courses that can enhance graduates' readiness to face the transformation of the auditing profession in the digital era.